Femoral head cartilage reconstruction using autologous osteochondral mosaicplasty: A case report. Issue 6 (10th February 2023) - Lee, Hyeonjoon; Kim, Hyoung Tae; Jo, Suenghwan
Abstract : Rationale: Cartilage injuries of the femoral head may occur following hip dislocation. As a rare injury, controversy persists regarding ideal treatment of damaged femoral head cartilage. Here we report the case of a patient who developed a large cartilage injury to the femoral head following anterior hip dislocation for which autologous osteochondral mosaicplasty with a graft harvested from the ipsilateral femoral head achieved a satisfactory outcome. Patient concerns: A 62-year-old man developed a right hip dislocation after a fall from a 5-m height and was referred to our institution. Diagnoses: The initial diagnosis was anterior hip dislocation. Upon hip joint reduction, a simple radiograph and computed tomography scan showed a large cartilage defect in the superolateral region of the femoral head. Multiple bony fragments were visible within the joint. Interventions: The hip joint was surgically dislocated. The large cartilage defect of the femoral head was treated with autologous mosaicplasty using an osteochondral autograft transfer system using multiple osteochondral plugs retrieved from a non-weight-bearing portion of the ipsilateral femoral head. Outcomes: Diagnostic hip arthroscopy performed at 8 months postoperative confirmed full incorporation of the osteochondral graft into the native femoral head. At the 2-year follow-up, the patient was pain-free, had a normal range of motion and displayed no evidence of osteoarthritis. Lessons: Isolated femoral head cartilage injuries may occur as a consequence of anterior hip dislocation. A femoral head with a large irregular cartilage defect can be treated with mosaicplasty using an osteochondral autograft from a non-weight-bearing portion of the ipsilateral femoral head.